MENGUKUR KEPUASAN KONSUMEN PRODUK SKIN CARE MELALUI KUALITAS PRODUK - Pauzy, Depy Muhamad; Sutrisna, Arga (Jurnal Ecoment Global, 2021)
This study aims to determine how the influence of product quality on customer satisfaction on skin care products. This research is descriptive and empirical. Descriptive research was conducted to obtain an overview of product quality and customer satisfaction. While empirical research was conducted to determine the relationship between variables through statistical calculations. Data collection techniques through questionnaires to 95 respondents by purposive sampling. The object of this research is Economics student at the Perjuangan University of Tasikmalaya. Research data will be analyzed using simple regression where product quality becomes the independent variable, and customer satisfaction as the dependent variable. The average use of skin care products used by Perjuangan University of Tasikmalaya is local skin care products. This is because the users of skin care products trust more what has been recommended by doctors, prefer and buy products that have guaranteed safety and are easily found in various places in Tasikmalaya. Based on the results of statistical tests obtained that product quality has a significant effect on customer satisfaction.Â Keywords: Skin Care; product quality, customer satisfaction.Â Keywords: Skin Care; product quality, customer satisfaction.